Voice Recognition And Control Of 3-Axis Robot Using Ai - G. Satya Sravanth, G.V.H. Kiran Reddy, B. Bharathi (International Journal of Advanced Science and Technology, 2020)
Communication between man-to-man is pretty common but the communication between the human and robot needs some technologies which works as an middleware between the human and the robot. In the existing system, there is no voice based control system is implemented , we have mobile based control of robot has been implemented so far. Voice proceesing os not yet  implemented  using  system  environment. We  have  only limited  speech  recognition keywords as training inputs are less. It is implemented in a normal Robot. We have only 5 commands in this implementation . In the modification work , we have deploy almost 11-12 controls using voice along with that we also include 3-axis robot control system using Artifical Intelligence(AI) and Deep Learning(DL). We can control the 3-Axis robot using the Android application.